Can Aidi injection alleviate the toxicity and improve the clinical efficacy of radiotherapy in lung cancer?: A meta-analysis of 16 randomized controlled trials following the PRISMA guidelines. Issue 35 (August 2016) - Xiao, Zheng; Liang, Rui; Wang, Cheng-qiong; Xu, Shaofeng; Li, Nana; He, Yuejuan; Tang, Fushan; Chen, Ling; Ma, Hu
Abstract: Background/Introduction: Aidi injection plus radiotherapy is widely used for lung cancer in China. Can Aidi injection alleviate the toxicity and improve the clinical efficacy of radiotherapy in lung cancer? Has Aidi injection the attenuation and synergistic efficacy to radiotherapy? There is lack of strong evidence to prove it. Objectives: To reveal its real attenuation and synergistic efficacy to radiotherapy and provide sufficient evidence for adjuvant chemotherapy strategies to lung cancer, we systematically evaluated all related studies. Data Sources: We collected all studies about Aidi injection plus radiotherapy for lung cancer in Medline, Embase, Web of Science, China national knowledge infrastructure database (CNKI), Chinese scientific journals full-text database (VIP), Wanfang database, China biological medicine database (CBM) (established to June 2015), and Cochrane Central Register of Controlled Trials (June 2015), evaluated their quality according to the Cochrane evaluation handbook of randomized controlled trials (5.1.0), extracted data following the PICO principles and synthesized the data by Meta analysis. Results: Sixteen randomized controlled trials (RCTs) with 1192 lung cancer patients were included, with general methodological quality in most trials. The merged relative risk (RR) values and their 95% CI of meta-analysis for objective response rate (ORR), disease control rate (DCR), and quality of life (QOL) were as follows: 1.54, (1.39, 1.70), 1.10 (1.02, 1.19), and 2.13 (1.68, 2.68). The merged RR values and their 95% CI of meta-analysis for myelosuppression and neutropenia, radiation pneumonitis, and radiation esophagitis were as follows: 0.51 (0.38, 0.69), 0.53 (0.42, 0.65), 0.52 (0.41, 0.67), and 0.52 (0.40, 0.68). All were statistically significant. The possibility of publication bias was small which objectively reported the results. Conclusions: The evidence available indicates that Aidi injection plus radiotherapy can significantly improve the clinical efficacy and QOL of patients with lung cancer. Aidi injection can alleviate the myelosuppression, radiation pneumonitis, and radiation esophagitis of radiotherapy. It has the attenuation and synergistic efficacy to radiotherapy. Abstract : Supplemental Digital Content is available in the text